Global scale arsenic pollution : increase the scientific knowledge to reduce human exposure - Muhammad Shahid (Éditions en environnement VertigO, 2018)
Arsenic contamination in water is a crucial human health and scientific challenge worldwide. Actually, high As levels above the recommended limit set by world health organization (10 µg/L) have been found in ground water of several countries around the world and millions of people have been exposed to As contaminated drinking water. The aim of the present paper is therefore to provide a synthesis of recent interdisciplinary knowledge on arsenic, in particular for urban gardeners and farmers who may be confronted with well water pollution or contamination of produced vegetables. The origins, chemical forms, routes of arsenic transfer and its impact on human health are discussed. Geogenic As contamination represents a major health threat in many countries, especially Asia. Advices are therefore finally proposed to avoid and reduce human exposure to arsenic in the context of urban agricultures.